Attitudes of general practitioners and their patients about ambulatory blood pressure monitoring in family medicine: Stališča zdravnikov družinske medicine in njihovih bolnikov do izvajanja 24-urnega neinvazivnega merjenja krvnega tlaka v ambulanti družinske medicine - Petek Šter, Marija; Kersnik, Janko (Acta Medico-Biotechnica, 2022)
Purpose: Ambulatory blood pressure monitoring (ABPM) is increasingly being used in general practice, but there is a lack of information about the attitudes of general practitioners and their patients about the use of ABPM in primary care in Europe.Methods: Cross sectional survey performed on consecutive patients with uncontrolled hypertension treated by at least two different antihypertensive drugs and referred for ABPM in 38 general practices in Slovenia. Patients and physicians completed a questionnaire about their satisfaction with, attitudes about and acceptance of ABPM in general practice; the latter two were assessed using 5 point Likert scales.Results: We obtained complete data for 185 patients; 95 female (51.4 %) and 90 (48.6%) male, aged 37 to 79 years (mean 59.5, SD 9.5 years). 106 (67.3 %) patients were completely satisfied with the instructions given before ABPM. Patients found ABPM an acceptable method of blood pressure control. They believed that ABMP helped to reach better bloodpressure control (Likert scale: 4.46, SD 1.03) and valued having access to ABPM in general practice (Likert scale: 4.65, SD 1.01). General practitioners strongly believed that ABPM wasacceptable to patients, improved patient and physician interest in blood pressure control, improved compliance with treatment and reduced prescription of antihypertensive drugs. They recognised ABPM as being most valuable in cases of patients with suspected white-coat hypertension (Likert scale: 4.79, SD 0.49).Conclusions: Patients and general practitioners find ABPM to be an acceptable method for investigating blood pressure. Patients value being able to access ABPM in general practice rather than in a specialist setting.